Interview with Line Matthiessen. (July 2013) - Matthiessen, Line
Line Matthiessen leads the Unit for Infectious Diseases and Public Health in the European Commission's Research and Innovation Directorate-General. Her unit promotes and supports EU research and innovation in the area of global health with emphasis on HIV/AIDS, malaria and tuberculosis, emerging epidemics, neglected infectious diseases and antimicrobial drug resistance, as well as activities in public health and health systems research. The Unit also supports the implementation of the European and Developing Countries Clinical Trials Partnership. Matthiessen was Head of Unit for coordination in the Directorate for Biotechnologies, Agriculture and Food Research from July 2007 to December 2010. She joined the European Commission in 1992. Matthiessen was trained as an MD at the University of Odense (Denmark) and received her PhD in Neurosciences from the University of Paris VI (France) in 1993. She spoke to Future Medicinal Chemistry regarding her career to date, how resistance has impacted neglected diseases and how the European Commission will tackle the issue of resistance in the coming years. Interview conducted by Isaac Bruce, Managing Commissioning Editor.